How Much Techne and How Much Praxis? In Quest of Practice as an Element of Improving Teacher’s Professionalism - Czerepaniak-Walczak, Maria (INSTED: Interdisciplinary Studies in Education & Society, 2012)
The text poses a question about teachers? workplace. It sounds like a heresy, but it is extremely important from the point of view of this profession. School is only one of venues of teachers? work and students? learning. Information openness and diversity of situations that create a learning possibility significantly distant teachers? workplaces from a classroom or an after-school club. This, in turn, forces us to view the practice from a wider perspective than ever and perceive it as an integral element of teachers? education. That means seeking concepts of such practices which will become a real source of teachers? competences, i.e. the knowledge about learning determinants and mechanisms, practical and cognitive skills used in the process of professional practice, abilities of autonomic and responsible performance of undertaken tasks and reflective self-evaluation. In this understanding the practices of teachers-to-be have not only educational functions, i.e. are a source of knowledge and skills that are necessary to be a teacher in various situations, but they are also a crucial circumstance of evaluating the appropriateness and candidates? success/failure in their future teaching job. This role of teachers? practices is often underestimated, neglected or simply unnoticed.